Prevalence of upper limb disorders and associated factors among workers in a Malaysian Public University (Call number FPSK(m) 2015 36) - Khudhir, Karwan Mahmood (2015)
A cross-sectional study was conducted among workers in Universiti Putra Malaysia (UPM) from May to September 2014. The main objective of this study was to determine the prevalence and associated factors of upper limb disorders among Universiti Putra Malaysia workers. Methodology: Respondents were selected randomly and a total of 271 workers who met the inclusion criteria participated in this study. Data were collected by face-to-face interview and posture assessment method based on Standardized Nordic Questionnaire (SNQ), Job Content Questionnaire (JCQ), and Rapid Upper Limb Assessment (RULA) method. Statistical analysis of data was carried out by using SPSS version 21. Result: The overall prevalence of ULDs among UPM workers was 67.2% and the highest prevalence by body parts were neck 147 (54.2%). Chi square test shows that 10 factors were significantly associated with ULDs; age (x 2=25.925, df=l, p<O.OOI), smoking (x2=19.728, df=l, p<O.OOI). BMI (x 2=169.643, df=l, p<O.OOI), physical activity (X2=124.662, df=l, p<O.OOl), duration of employment, (X2=17.567, df=l, p<O.OOI), awkward posture (x2=75.640, df=l,p<O.OOl), control at work (x2=34.775, df=1, p<O.OOl), psychological demand (X2=64.938, df=l, p<O.OOl), social support (X2=37.736, df=l, p<O.OOI), and job satisfaction (X2=95.817, df=l, p<O.OOl). Multiple logistic regression test showed the significant risk factors for ULDs were obese (OR=19,472, 95%CI: 5.396-70.273), infrequent physical activity (OR=5.756,95%CI: 1.504-22.028), medium and very high RULA risk level (OR=12.242,95%CI: 3.617-41.435). Conclusion: Among UPM workers the overall prevalence of upper limb disorders was high arid significantly associated with age, smoking, BMI, physical activity, duration of employment, awkward posture, control at work,psychological demand, social support, and job satisfaction. In order to reduce the risk ofULDs among UPM workers effective prevention strategies are required.